Renormalised solutions in thermo-visco-plasticity for a Norton–Hoff type model. Part II: The limit case. (October 2016) - Chełmiński, Krzysztof; Owczarek, Sebastian
Abstract: In this article we define a new notion of solutions in thermo-visco-plasticity. Using results from our previous work Chełmiński and Owczarek (2016) we analyse the limit case and prove existence of renormalised solutions to the considered problem assuming that the inelastic constitutive function is of the Norton–Hoff type.